1999
DOI: 10.1088/0953-8984/11/18/309
|View full text |Cite
|
Sign up to set email alerts
|

The systematic study of the normal-state transport properties of Bi-2212 crystals

Abstract: The temperature dependences of the in-plane resistivity ab(T ) and out-of-plane resistivity c(T ) in Bi-2212 crystals covering the region from the underdoped to the overdoped regime have been measured. In the underdoped regime, ab(T ) deviates from a linear temperature dependence below a characteristic temperature T *, well above Tc, whose value decreases with increasing hole concentration. For underdoped crystals, ab(T) shows a typical S-shaped temperature dependence and ab = 0*+exp(-/T ) is satisfactorily ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…9 above T * as shown with ✷ lacks the T -linear metallic behavior if observed closely and also give ∆P G = −57 K. Leridon et al [11] B2, Carrington et al [11] Eq. ( 15) and ( 16) ρ ab (mΩ.cm) D4, Ruan et al [12] C3, Ruan et al [12] Eq. ( 15) and ( 16) Eq.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 above T * as shown with ✷ lacks the T -linear metallic behavior if observed closely and also give ∆P G = −57 K. Leridon et al [11] B2, Carrington et al [11] Eq. ( 15) and ( 16) ρ ab (mΩ.cm) D4, Ruan et al [12] C3, Ruan et al [12] Eq. ( 15) and ( 16) Eq.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, 2D ∆ P G in c-axis normal state conduction that could be thought of as a function of doping, be it ionic substitution or oxygen content, extends to ab-planes and becomes 3D due to increasing ∆ P G with decreasing oxygen content or certain ionic substitution. Such properties in Y123 [11] and Bi2212 [12] samples with different oxygen content (7−δ) and Ca 2+…”
Section: Introductionmentioning
confidence: 99%
“…42 In this context, the minimum T c observed has been T c ≈ 35 K, corresponding to y = 0.42 and to a room-temperature resistivity ρ ≈ 20 × 10 −6 Ω m. Similar results (T c ≈ 50 K and ρ ≈ 30 × 10 −6 Ω m at room temperature) have been obtained by a parallel systematic study. 41 Although we have not performed a systematic study as a function of CD and CF so far, a preliminary comparison between the Bi-2212 properties emerging from our heaviest irradiation conditions (i.e., T c ≈ 48 K and ρ ≈ 64 × 10 −6 Ω m, see also Figure S5 in the Supporting Information) and the ones obtained by means of cation substitution shows that the UD status induced in our case substantially preserves the same value of T c even if the normal-state resistivity is larger by at least a factor of 2. This observation seems to suggest that, given the same level of normal-state resistivity ρ, the Bi-2212 underdoping process via irradiation preserves the superconducting properties more than cation substitution.…”
Section: Data Treatments Results and Discussionmentioning
confidence: 99%
“…More often, UD crystals have been obtained by means of a postannealing stage with very low oxygen partial pressure (or vacuum). Typically, these procedures result in only moderately UD samples with T c ≥ 65 K. ,, This is the reason why the partial substitution of 3+ valence atoms for 2+ cations (e.g., Bi 3+ for Sr 2+ , or Y 3+ for Ca 2+ ) has been tried several times to induce arbitrary small doping regimes. By means of this technique, it has been possible to systematically explore the full doping range of Bi 2 Sr 2 Ca 1– y Y y Cu 2 O 8 from OD to UD all the way down to the insulating behavior, detecting the metal–insulator transition at y = 0.45 . In this context, the minimum T c observed has been T c ≈ 35 K, corresponding to y = 0.42 and to a room-temperature resistivity ρ ≈ 20 × 10 –6 Ω m. Similar results ( T c ≈ 50 K and ρ ≈ 30 × 10 –6 Ω m at room temperature) have been obtained by a parallel systematic study .…”
Section: Data Treatments Results and Discussionmentioning
confidence: 99%
“…It was found that the critical concentration x c of La for quenching superconductivity can be extended above 0.30 for both series, which is higher than that reported (0.25). [8][9][10][11][12][13][14][15][16][18][19][20][21][22]26,52,53 It was also clear that La slightly had a higher solubility in the 2212 series, and it was less detrimental to the superconductivity as compared to the 2223 series; that is [T c (x)/T c (0)] α (1/T c ) for BSCCO systems.…”
Section: Resistivity Analysismentioning
confidence: 99%